2022
DOI: 10.3390/rs14195042
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Radar Echo Space-Time Sequence Based on Improving TrajGRU Deep-Learning Model

Abstract: Nowcasting of severe convective precipitation is of great importance in meteorological disaster prevention. Radar echo extrapolation is an effective method for short-term precipitation nowcasting. The traditional radar echo extrapolation methods lack the utilization of radar historical data as well as overlooking the nonlinear motion of small- to medium-sized convective systems in radar echoes. To solve this, we propose a deep-learning model combining CNN and RNN. The model T-UNet proposed in this paper uses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In the echo extrapolation task of deep learning, the commonly used loss function was the mean square error (MSE), but a large number of studies had shown that it tends to cause blurring of the predicted images, making the extrapolation of strong echoes less effective [30,31]. The balanced mean square error (BMSE) could somewhat attenuate the blurring of the prediction images caused by the increase of the forecast lead time [23]. Therefore, in this study, the MSE and BMSE loss functions were used to carry out the model training, respectively, and compare the effects of different loss functions on the prediction.…”
Section: Loss Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the echo extrapolation task of deep learning, the commonly used loss function was the mean square error (MSE), but a large number of studies had shown that it tends to cause blurring of the predicted images, making the extrapolation of strong echoes less effective [30,31]. The balanced mean square error (BMSE) could somewhat attenuate the blurring of the prediction images caused by the increase of the forecast lead time [23]. Therefore, in this study, the MSE and BMSE loss functions were used to carry out the model training, respectively, and compare the effects of different loss functions on the prediction.…”
Section: Loss Functionmentioning
confidence: 99%
“…According to Hu et al [18], the main benefits of U-Net are its straightforward structure and adaptability to task requirements, which makes it possible to provide more precise small-scale rainfall nowcasting. Therefore, many scholars have restructured and improved the U-Net model in terms of convolutional blocks, sampling layers, skip connection layers, and attention mechanisms to make it suitable for the echo extrapolation task, and compared it with the traditional echo extrapolation methods and reference models to show the good performance of the optimized model [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Due to meteorological features such as cloud convection, there has been a significant misalignment between the two images ,as shown in the sequence of 15 radar echo images in one and a half hours in Figure 3 Even the improvement proposed in this article is rooted in the fusion and enhancement of these five models. For instance, PredRNN++, E3DLSTM, MIM, PFST-LSTM, SmaAt-UNet [24][25][26][27][28][29] primarily focus on two aspects for improvement. Firstly, they optimize the network architecture by incorporating gradient highways and Unet models.…”
Section: Aconvlstm and Convgrumentioning
confidence: 99%
“…Among them, the centroid tracking method is primarily suitable for tracking strong echoes and making short-term predictions. When radar echoes are scattered or exhibit merging and splitting phenomena, the accuracy of extrapolation forecasts is significantly affected [10][11][12]. The cross-correlation method assumes that the evolution of echoes is linear and tracks the echo regions based on the optimal correlation coefficients between neighboring temporal regions.…”
Section: Introductionmentioning
confidence: 99%